Prognostic importance of radiologic extranodal extension in HPV-positive oropharyngeal carcinoma and its potential role in refining TNM-8 cN-classification. (March 2020) - Huang, Shao Hui; O'Sullivan, Brian; Su, Jie; Bartlett, Eric; Kim, John; Waldron, John N.; Ringash, Jolie; de Almeida, John R.; Bratman, Scott; Hansen, Aaron; Bayley, Andrew; Cho, John; et al.
Highlights: Radiologic extranodal extension (rENE) is a strong prognostic factor in HPV+ OPC. Inclusion of rENE in TNM-8 cN-classification improves outcome prediction. HPV+ OPC Patients with rENE is not suitable for deintensification trials. rENE can be reliably ascertained with satisfactory inter-/intra-rater concordance. Abstract: Purpose: This study examines outcome heterogeneity and potential to refine the TNM-8 cN-classification using radiologic extranodal extension (rENE) in a contemporary HPV-positive (HPV+) oropharyngeal carcinoma (OPC) cohort. Methods: All HPV+ OPC treated with definitive IMRT from 2010-2015 were included. Pre-treatment CT/MR of cN+ cases were reviewed by a head-neck radiologist for rENE. Overall survival (OS) and disease-free survival (DFS) were compared between rENE-positive (rENE+) vs rENE-negative (rENE−). Multivariable analysis (MVA) for OS confirmed the prognostic value of rENE. Refined cN-classifications for new TNM staging proposals were evaluated against TNM-8 using established criteria. Results: A total of 517 cN+ (rENE+: 97; rENE−: 420) and 41 cN0 cases were identified. The rENE+ proportion increased with rising N-category (N1/N2/N3: 11%/19%/84%, p < 0.001). Median follow-up was 5.1 years. Compared to rENE−, rENE+ patients had a lower 5-year OS (56% vs 85%) and DFS (46% vs 83%) overall, and in N1 (OS: 57% vs 89%; DFS: 51% vs 87%) and N2 subsets (OS: 45% and 76%; DFS: 33% vs 74%) (all p < 0.001). MVA confirmed the prognostic value of rENE for OS (HR = 3.86, p < 0.001) and DFS (HR = 3.89, p < 0.001). We proposed two new cN-classifications: Schema1 reclassified any N_rENE+ as New_N3 ; Schema2 reclassified N1_rENE+ as New_N2 and N2_rENE+ as New_N3 . Stage incorporating either Schema1 (ranked 1st) or Schema2 (ranked 2nd) cN- categories outperformed TNM-8. Conclusion: This study confirms that rENE is prognostically important and facilitates understanding of known outcome heterogeneity within TNM-8 in HPV+ OPC patients. rENE is a promising parameter to refine the TNM-8 cN-classifications.